Characterization of CDR® plus NACC FTLD at Phenoconversion from Asymptomatic to Mild Behavioral and/or Cognitive Impairment in Familial Frontotemporal Lobar Degeneration: Data from the ALLFTD Consortium. (20th December 2022) - Miyagawa, Toji; Brushaber, Danielle; Syrjanen, Jeremy A.; Kremers, Walter K.; Fields, Julie A.; Forsberg, Leah K.; Heuer, Hilary W.; Huey, Edward D.; Knopman, David S.; Kornak, John; Boxer, Adam L.; Rosen, Howard J.; et al.
Abstract: Background: The three most common genes responsible for the familial Frontotemporal Lobar Degeneration (f‐FTLD) are MAPT, GRN, and C9orf72, with the C9orf72 mutation being the most common cause of f‐FTLD. The ALLFTD Consortium targets to characterize f‐FTLD, including its preclinical stage, to prepare for clinical trials in FTLD. We sought to investigate the initial symptoms and clinical picture of f‐FTLD and compare them among the common pathogenic genes using longitudinal CDR® plus NACC FTLD. Method: We longitudinally assessed the CDR® plus NACC FTLD among 292 asymptomatic participants of the ALLFTD Consortium who are family members of f‐FTLD caused by MAPT (n = 99), GRN (n = 67), or C9orf72 (n = 126) mutations, and described the detailed profiles of the CDR® plus NACC FTLD in the participants who developed Mild Behavioral and/or Cognitive Impairment (MBCI). Result: Forty‐one participants (17 MAPT, 11 GRN, 13 C9orf72 ) developed MBCI during follow‐up visits . Age at the diagnosis of MBCI was 52.3±13.0 years ( GRN 63.2±11.8, MAPT 43.5±8.6, C9orf72 54.7±10.7). Frequencies of abnormal rating on the eight CDR® plus NACC FTLD domains at the time of MBCI diagnosis were: "Memory" 44% ( MAPT 47%, GRN 55%, C9orf72 31%); "Orientation" 7% ( MAPT 6%, GRN 9%, C9orf72 8%); "Judgment and Problem Solving" 39% ( MAPT 41%, GRN 55%, C9orf72 23%); "Community Affairs" 22% ( MAPT 24%, GRN 18%, C9orf72 23%); "Home and Hobbies" 22% ( MAPT 35%, GRN 0%, C9orf72 23%); "Personal Care" 0%; "Behavior/Comportment/Personality" 51% ( MAPT 59%, GRN 55%, C9orf72 38%); "Language" 29% ( MAPT 18%, GRN 55%, C9orf72 23%). Conclusion: Initial symptoms and clinical picture of f‐FTLD in MBCI stage differ among responsible FTLD genes, which could be useful in detecting very early features of f‐FTLD in pathogenic mutation carriers.